Diagnostic of Innovations and Volatility Persistence in Emerging Markets : Evidence from Sukuk and Stock Indices - Widad, Metadjer; Benbekhti Seyf Eddine; Boulila Hadjer (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This paper analysis the persistence of shock and volatility of both Islamic and conventional financial markets, as well as the natural correlation between those markets. This study used the Bivariate BEKK-GARCH (1,1) model to examine the persistence of shock and volatility based on the daily prices in Dubai Islamic Capital Market (Sukuk index) and conventional Stock Market (DFM index). The results showed that both Sukuk and stock market indices were affected by their own news, while the volatility was persistent during the period of this research. The study also found a negative correlation between prices in both Sukuk and Stock markets during the Dubai debt crisis indicating that Islamic bonds were considered as a good portfolio diversifier. This study defines the natural correlation between the daily prices of both Sukuk and stock market, unlike the other studies which used returns. In addition, the empirical results might be valuable for investors and market makers to ensure a good portfolio diversification strategy